A Learning Architecture: How School Leaders Can Design for Learning Social Justice. (April 2013) - Scanlan, Martin
Purpose: The field of socially just educational leadership focuses on reducing inequities within schools. The purpose of this article is to illustrate how one strand of social learning theory, communities of practice, can serve as a powerful tool for analyzing learning within a school ostensibly pursuing social justice. The author employs a core dimension of the theory of communities of practice, "learning architecture, " as a conceptual framework to analyze one such school.Research Design: For the case study presented here, data were collected in the form of interviews with teachers, administrators, support staff, and volunteers and board members ( N = 21), field observations, and archival documents in an elementary school over the course of a school year.Findings: Members within a school community belong to multiple, overlapping, and interacting "communities of practice, " groupings of individuals who share common interests, practices, and purposes. The learning architecture illuminates design features that affect learning within and across these communities of practice. These features both facilitate and frustrate the efforts of individual teachers, administrators, support staff, and volunteers and board members to pursue social justice.Conclusions: This research suggests that the theory of communities of practice, and in particular the learning architecture therein, can be a valuable analytical tool within the field of socially just educational leadership, providing a perspective on how individuals within school communities learn to better serve traditionally marginalized students, along with the interconnections, depth, and edges to this learning.